Excess Mortality in Italy During the COVID-19 Pandemic: Assessing the Differences Between the First and the Second Wave, Year 2020 - Dorrucci, Maria; Minelli, Giada; Boros, Stefano; Manno, Valerio; Prati, Sabrina; Battaglini, Marco; Corsetti, Gianni; Andrianou, Xanthi; Riccardo, Flavia; Fabiani, Massimo; Vescio, Maria Fenicia; Spuri, Matteo; et al. (Frontiers in Public Health, 2021)
COVID-19 dramatically influenced mortality worldwide, in Italy as well, the first European country to experience the Sars-Cov2 epidemic. Many countries reported a two-wave pattern of COVID-19 deaths, however studies comparing the two waves are limited. The objective of the study was to compare all-cause excess mortality between the two waves occurred during the year 2020 using Nationwide data. Excess all-cause deaths were estimated using negative binomial models with time modelled by quadratic splines. The models were applied also to estimate excess all-cause deaths “not directly attributable to COVD-19”, i.e. without a previous COVID-19 diagnosis. During the first wave (February 25- May 31), we estimated 52 437 excess deaths (95% CI: 49 213 – 55 863) and 50 979 (95% CI: 50 333 – 51 425) during the second phase (October 10 – December 31), corresponding on percentage terms, respectively to 34.8% (95% CI: 33.8% - 35.8%) in the second and of 31.0% (95%CI: 27.2% - 35.4%) in the first. During both waves, all-cause deaths excess percentages were higher in Northern regions (59.1% during the first and 42.2% in the second), with significant increase in the rest of Italy (from 6.7% to 27.1%) during the second wave. Males and those aged 80 or over were the most hit groups with an increase in both during the second wave. Excess deaths not directly attributable to COVID-19 decreased during the second respect to the first phase, respectively: from 10.8% (95% CI: 9.5% -12.4%) to 7.7% (95% CI: 7.5% - 7.9%). The percentage increase in excess deaths from all causes suggests in Italy a different impact of the SARS-CoV-2 virus during the second wave in 2020. The decrease in excess deaths not directly attributable to COVID-19 may indicate an improvement in the preparedness of the Italian health care services during this second wave, in the detection of COVID-19 diagnoses and/or clinical practice towards the other severe diseases.